House of cards a tale of hubris and wretched excess on Wall Street - Cohan, William D. frey50 (Waterville, Me. : Thorndike Press / Gale Cengage Learning, 2009)
Chronicles the fall of Bear Stearns, portraying the players and factors that ultimately led to the collapse of the global financial markets.
Keywords: Bear, Stearns & Co; Investment banking -- United States; Bank failures -- United States; Financial crises -- United States